Assessment of Genetic Diversity of Rice Landraces in Southern Border Provinces Using RAPD and HAT-RAPD Techniques - วัฒนาพันธ์ นรารัตน์; ศรีช่วย วุฒิชัย (Princess of Naradhiwas University Journal, 2018)
Rice (Oryza sativa L.) is the main food source for population, and the important export of Thailand. Due to the geographical and climatic difference of each region, the diversity of native plant including rice in southern Thailand has also been shown. This research aims to study the diversity of native rice grown in southern border provinces by using RAPD and HAT-RAPD techniques. Base on RAPD technique, 2 groups of rice were shown. The first group composted of Hom kradang nga rice and, Seebookantang rice, for the second group is Sang yod rice and Leb nok Pattani rice. Meanwhile, HAT-RAPD technique provided a group of of Hom kradang nga rice, Seebookantang rice and Leb nok Pattani rice, and Sang yod rice was separated into the second group. Moreover, applying primer from RAPD with HAT-RAPD technique, and using HAT-RAPD primer with RAPD technique provided the same results of RAPD technique. Therefore, the suitable technique for each plant needed for study on variety of rice relationship to be useful for further cultivars improvement